CCL22 Prevents Rejection of Mouse Islet Allografts and Induces Donor-Specific Tolerance. Issue 10 (October 2015) - Montane, Joel; Obach, Merce; Alvarez, Sigrid; Bischoff, Loraine; Dai, Derek L.; Soukhatcheva, Galina; Priatel, John J.; Hardenberg, Gijs; Levings, Megan K.; Tan, Rusung; Orban, Paul C.; Verchere, C. Bruce
Manipulation of regulatory T cell (Treg) migration by islet expression of the chemokine CCL22 prevents diabetes in NOD mice and delays recurrent autoimmunity in syngeneic islet transplants. We sought to determine whether attracting Tregs with CCL22 also prevents islet allograft rejection. Isolated Bl/6 mouse islets were transduced overnight with adenovirus expressing CCL22 (Ad-CCL22) downstream of the CMV promoter. Islets were transplanted under the renal capsule of Balb/c recipients made diabetic by streptozotocin. To assess immunologic tolerance, graft-bearing kidneys from recipients of CCL22-expressing islet grafts were removed, and mice received a second transplant of naive islets from the same donor strain or third-party islets into the contralateral kidney. Adenoviral expression of CCL22 conferred prolonged protection of islet allografts in MHC-mismatched, diabetic recipients, maintaining normoglycemia in 75% of recipients for at least 80 days. Increased frequency of Treg cells was observed in islet grafts transduced with Ad-CCL22 compared with untreated grafts. Normoglycemic recipients of CCL22-expressing islet grafts showed complete absence of antidonor antibodies and no lymphocyte proliferation after exposure to donor splenocytes. After removal of the primary graft at day 80, mice that received a second transplant with untreated islets from the same donor strain did not reject the grafts, suggesting the development of tolerance. Expression of CCL22 recruits Treg cells to transplanted islets, prevents activation of alloreactive T-cells and islet allograft failure and induces alloantigen-specific tolerance. Manipulation of Treg cells by CCL22 in transplanted islets may be a novel therapeutic strategy for diabetes.